Sublethal effects of neonicotinoids in bees: a review - N. C. Pereira (Scientific Electronic Archives, 2020)
Beginning in 2006, beekeepers on the east coast of the United States began to report severe declines in their honeybee colonies. Because of the severity and unusual circumstances of these declines, scientists have called this phenomenon colony collapse disorder (CCD). In 2019, 500 million dead bees were found in Brazil. Analyzes of dead bees identified agrochemicals in approximately 80% of them. Thus, it is believed that one of the main causes for CCD is the intensive use of agrochemicals. Neonicotinoids are the most widely used class of insecticides in the world, they are used for pest control in a variety of crops. However, they can not only affect insects considered pests, but also non-target organisms, such as pollinators. This class of insecticides is divided into five main active ingredients: imidacloprid, thiamethoxam, clothianidin, thiacloprid and acetamiprid. Several studies demonstrate that sublethal concentrations of these insecticides affect bees in different ways, such as navigation memory and muscle movements. Thus, this review aims to report the studies published between 2014 and 2019 regarding the contamination of bees with sublethal doses of the five active ingredients of the neonicotinoid class. Imidacloprid and thiamethoxam are the most used insecticides of this class and show high toxicity to bees. On the other hand, clothianidin showed the least sublethal effects on bees on the studies reported on this review. Thiacloprid and acetamiprid, although less used in agriculture, also impair several aspects of bee health. Thus, it is possible to infer that neonicotinoids are contributing to the disappearance of bees worldwide.